The Influence of Processing Methods on Corrosion Rates of Magnesium - Carbon Nanotube Nanocomposites: A Short Review - Thornby, Jiselle; Alshami, Ali; Haghshenas, Meysam (Current Nanomaterials, 2021)
Several studies have reported the corrosion rates of magnesium carbon nanotube nanocomposites, but their corrosion behavior is still not well understood. Adding carbon nanotubes (CNTs) to magnesium (Mg) matrices almost always results in an increase in mechanical properties, e.g., increased elastic modulus, hardness, ultimate tensile strength, and yield strength. However, this increase in mechanical properties usually comes at the expense of compromised corrosion resistance. Galvanic interactions between the carbon nanotubes and the magnesium matrix are the usual culprits of nanocomposite corrosion. It is important to study the corrosive behavior of these materials further to create a nanocomposite that is less susceptible to corrosion from the start, i.e., by careful selection of the fabrication method. In the present review, four processing methods (Disintegrated Melt Deposition, Friction Stir Processing, Powder Metallurgy, and Ball Milling), which were used to successfully synthesize magnesium carbon nanotube nanocomposites and test their corrosive properties are discussed. Attempts are made to correlate processing methods to corresponding corrosion rates. It was found that the corrosion rates extracted from each reviewed study may not be readily comparable, and by looking into nanocomposite coatings and carbon nanotube, it was found that volume or weight percent optimization may be the best way to proceed. The findings of this investigation can be used as a starting point for the creation of a magnesium carbon nanotube nanocomposite, which is less inherently susceptible to corrosion as this could take the “potential” out of the many potential applications of these novel materials.
Keywords: corrosion